Chasing the Collaborative: Critical Studies of Performer Agency in Modern Flute Music - Habbestad, Bjørnar (Oslo NMH, 2022)
How are developments in musical materiality connected to changes in the way composers and performers collaborate? This thesis is a search for traces of collaborative practice within the creation and performance of modern flute music from three perspectives: historical musicology, interview-based research and artistic research. From the perspective of historical musicology I trace the history of one of the first novel instrumental techniques for flute. My understanding of these developments is then deepened through the analysis of extensive research interviews with flutist Roberto Fabbriciani. Finally, the findings from these two processes are operationalized in a sequence of performance-based research, in which I explore, experiment with and extend the different practices connected to the flute part of Luigi Nono’s Das atmende Klarsein. In a complementary fashion, these elements exemplify how the advent of experimental methods and collaborative practice have influenced and changed the role played by performers in the creation of music, necessitating a rethinking of the notion of performer agency in music. These changes are traced in historical sources, verbalized in interviews, and investigated through artistic research.
Dissertation for the PhD degree at the Norwegian Academy of Music.
Keywords: Nono, Luigi -- 1924-1990; Flute; Performance; Musical analysis; Artistic research